Validity and test-retest reliability of the TIVRE-Basket test for the determination of aerobic power in elite male basketball players - Vaquera, A.; Villa, J. G.; Morante, J. C.; Thomas, G.; Renfree, A. J.; Peters, D. M. (The Journal of Strength and Conditioning Research, 2016)
The aims of this study were to (a) determine the relationship between performance on the court-based TIVRE-Basket test and peak aerobic power determined from a criterion laboratory-based incremental treadmill test and (b) to examine the test-retest reliability of the TIVRE-Basket test in elite male basketball players. To address aim 1, 36 elite male basketball players (age: 25.2 ± 4.7 years, weight: 94.1 ± 11.4 kg, height: 195.83 ± 9.6 cm) completed a graded treadmill exercise test and the TIVRE-Basket within 72 hours. The mean distance recorded during the TIVRE-Basket test was 4001.8 ± 176.4 m, and mean VO2 peak was 54.7 ± 2.8 ml/kg/min, and the correlation between the 2 parameters was r = 0.824 (p = 0.001). Linear regression analysis identified TIVRE-Basket distance (in meters) as the only unique predictor of VO2 peak in a single variable plus constant model: VO2 peak = 2.595 + (0.13 × TIVRE-Basket distance [in meters]). Performance on the TIVRE-Basket test accounted for 67.8% of the variance in VO2 peak (t = 8.466, p = 0.001, 95% confidence interval: 0.01-0.016, SEE: 1.61). To address aim 2, 20 male basketball players (age: 26.7 ± 4.2 years, height: 1.94 ± 0.92 cm, weight: 94.0 ± 9.1 kg) performed the TIVRE-Basket test on 2 occasions. There was no significant difference in total distance covered between trial 1 (4138.8 ± 677.3 m) and trial 2 (4188.0 ± 648.8 m; t = 0.5798, p = 0.5688). Mean difference between trials was 49.2 ± 399.5 m, with an intraclass correlation coefficient of 0.85 suggesting a moderate level of reliability. Standardized typical error of measurement was 0.88%, representing a moderate degree of trial-to-trial error, and the Coefficient of Variation (CV) was 6.3%. The TIVRE-Basket test therefore represents a valid and moderately reliable court-based sport-specific test of aerobic power for use with individuals and teams of elite-level male basketball players. Future research is required to ascertain its validity and reliability in other basketball populations, for example, across age groups, at different levels of competition, in females and in different forms of the game, for example, wheelchair basketball.